Science and technology studies of the causes of prohibited foods in Islamic law - Alvi Jauharotus Shukriya; Hayyun Durrotul Faridah (Journal of halal product and research (JPHR), 2019)
Development of science and technology have increasing rapidly. Almost all aspects have undergone modernization including research in Islamic aspects. Many studies have concluded that facts about the causes of food are permitted or prohibited by Islamic law. Al-Quran and Hadith have regulated permitted or prohibited foods. Obeying the prohibition for not consume prohibited food is believed contain wisdom and goodness for Muslims. This study will discuss scientific reasons that prohibited food in Islamic lawa has a negative impact on human health. This research refers to the main sources of Islamic law, namely the Holy Quran and Hadith, and scientific studies that prove the existence of negative effects on prohibited food for human health. This study showed that, prohibited foods in Islamic law are indeed not suitable for consumption and endanger human health, such as the presence harmful bacteria in carcass, dangerous compound in blood, parasitic diseases in pig, organ damage due to consume khamr and danger of meat consumption that is not slaughtered according to Islamic law.